2017
DOI: 10.1016/j.drugalcdep.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Age of first drunkenness and risks for all-cause mortality: A 27-year follow-up from the epidemiologic catchment area study

Abstract: Background Early-onset drunkenness is associated with an increased risk of developing an alcohol use disorder (AUD), which predicts excess mortality risk. Here, we estimated mortality risk for drinkers with and without early drunkenness. Methods For 14,848 adult participants interviewed about drinking, drunken episodes, and AUD in 1981–83 for the Epidemiologic Catchment Area in New Haven (Connecticut), Baltimore (Maryland), St. Louis (Missouri), and Durham (North Carolina), we linked National Death Index rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Publish research confirms that age of reporting first being drunk is related to the negative effects of drinking [50]. Early-onset drunkenness is associated with an increased risk of developing alcohol use disorder and signaled excess mortality risk [51]. Consistent with these earlier reports, our results showed that the younger the age of first drunkenness, the greater the likelihood of becoming a moderate or heavy drinker.…”
Section: Discussionsupporting
confidence: 90%
“…Publish research confirms that age of reporting first being drunk is related to the negative effects of drinking [50]. Early-onset drunkenness is associated with an increased risk of developing alcohol use disorder and signaled excess mortality risk [51]. Consistent with these earlier reports, our results showed that the younger the age of first drunkenness, the greater the likelihood of becoming a moderate or heavy drinker.…”
Section: Discussionsupporting
confidence: 90%
“…The control variables were age in years (variable CATAG6; 18–25, 26–34, 35–49, 50–64 or 65 or older); sex (variable IRSEX; male or female); sexual orientation (variable SEXIDENT; heterosexual, lesbian or gay, bisexual); ethnoracial identity (variable NEWRACE2; non-Hispanic White, non-Hispanic African American, non-Hispanic Native American/Alaska Native, non-Hispanic Native Hawaiian/Pacific Islander, non-Hispanic Asian, non-Hispanic more than one race or Hispanic); educational attainment (variable IREDUHIGHST2; 5th grade or less, 6th grade, 7th grade, 8th grade, 9th grade, 10th grade, 11th or 12th grade completed, High school diploma/GED, some college credit but no degree, Associate’s degree, College degree or higher), annual household income (variable INCOME; less than US$20,000, US$20,000–49,999, US$50,000–74,999 or US$75,000 or more); marital status (variables IRMARITSTAT and IRMARIT recoded; married, divorced/separated, widowed or never married); self-reported engagement in risky behaviour (variable RSKYFQTES recoded; never, seldom, sometimes or always), lifetime cocaine use (variable COCFLAG; ever used or never used), lifetime other stimulant use (variable STMANYFLAG; ever used or never used), lifetime sedative use (variable SEDANYFLAG; ever used or never used), lifetime tranquilizer use (variable TRQANYFLAG; ever used or never used), lifetime heroin use (variable HERFLAG; ever used or never used), lifetime pain reliever use (variable PNRANYFLAG; ever used or never used), lifetime marijuana use (variable MRJFLAG; ever used or never used), lifetime phencyclidine (PCP) use (variable PCPFLAG; ever used or never used), lifetime 3,4-methylenedioxymethamphetamine (MDMA/ecstasy) use (variable ECSTMOFLAG; ever used or never used), lifetime inhalant use (variable INHALFLAG; ever used or never used), lifetime smokeless tobacco use (variable SMKLSSFLAG; ever used or never used), lifetime pipe tobacco use (variable PIPFLAG; ever used or never used), lifetime cigar use (variable CGRFLAG; ever used or never used), lifetime daily cigarette use (variable CDUFLAG; ever used or never used) and age of first alcohol use (variable IRALCAGE recoded; less than 13 years of age (Preteen), 13–19 years of age (Teen), more than 19 years of age (Adult), or never used). These control variables were coded as separate covariates and broadly mirror the covariates of prior investigations ( Hendricks et al, 2015 ; Sexton et al, 2019b ), except for lifetime smokeless tobacco, pipe tobacco, cigar and daily cigarette use, as well as age of first alcohol use, which were added to control for a lifetime history of major health risk factors ( Christensen et al, 2018 ; Hu et al, 2017 ; Inoue-Choi et al, 2019a , 2019b ; Levola et al, 2020 ). Lastly, a recoded version of the Kessler Psychological Distress Scale ( Kessler et al 2002 , 2010 ) was also included as a control variable (variable K6SCMON recoded into dichotomous variable), but only in the ordered logistic regression model predicting self-reported overall health (see below) to ensure that self-reported overall health was not influenced by the mental health status of the respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Studies support the finding that the younger a person starts drinking alcohol (DeWit, Adlaf, Offord, & Ogborne, 2000;Grant, Stinson, & Harford, 2001;Hu, Eaton, Anthony, Wu, & Cottler, 2017;LaBrie, Rodrigues, Schiffman, & Tawalbeh, 2008;White & Hingson, 2014) and the earlier a person experiences his or her first alcohol intoxication Hingson, Heeren, Zakocs, Winter, & Wechsler, 2003;Morean et al, 2014), the more likely alcohol is to have a significant and lasting negative impact on his or her life. The results from the current study appear to support this assessment.…”
Section: Comparative Assessmentmentioning
confidence: 88%